Los efectos jurídicos de la suspensión condicional de la pena en la legislación penal ecuatoriana - Contreras Domínguez, Douglas Anthony (2018)
The conditional suspension of the sentence established in our noble Integral Organic Criminal Code, (IOCC), was published in its official register No. 180 on Monday February 10, 2014 and came into force August 10, 2014, is an alternative measure to the criminal conflict in which the sentenced person at first instance can avail this measure as long as a series of requirements stipulated in article 630 and others of the Integral Organic Criminal Code. This petition can be done in the same trial hearing or within the next twenty - four hours. It is important to mention that the conditional suspension of the sentence can only be executed in crimes whose deprivation of liberty does not exceed 5 years and shall not proceed in crimes against sexual and reproductive integrity, violence against women or family members……….